2014
DOI: 10.1111/asj.12300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary star anise (Illicium verumHook f) supplementation during gestation and lactation on the performance of lactating multiparous sows and nursing piglets

Abstract: Thirty-two sows were allocated to four treatments to evaluate the effect of dietary star anise (SA) supplementation during gestation and lactation on the lactational performance of sows. At 85 days of gestation, sows were randomly allotted to one of two diets supplemented with 0.5% SA or basal diet. After farrowing, sows were further allotted to one of two lactation diets supplemented with 0.5% SA or basal diet. On a weekly basis, body weight (BW) of sows and piglets was measured. Blood and milk samples were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Rao et al (2012) reported that star anise has significant potential to be used as a natural antioxidant agent. I. verum powder or oil was shown to increase the antioxidant capacities of lactating multiparous sows (Wang et al, 2015), laying hens (Yang et al, 2017;Yu et al, 2018) and broilers (Ding, Yang, Yang, 2017;Ding, Yang, Yi, et al, 2017), which is consistent with the results of this study. Bhatti et al (2017) reported that protocatechuic acid in I. verum has excellent antioxidative properties.…”
Section: Tnfα Nrf2supporting
confidence: 91%
“…Rao et al (2012) reported that star anise has significant potential to be used as a natural antioxidant agent. I. verum powder or oil was shown to increase the antioxidant capacities of lactating multiparous sows (Wang et al, 2015), laying hens (Yang et al, 2017;Yu et al, 2018) and broilers (Ding, Yang, Yang, 2017;Ding, Yang, Yi, et al, 2017), which is consistent with the results of this study. Bhatti et al (2017) reported that protocatechuic acid in I. verum has excellent antioxidative properties.…”
Section: Tnfα Nrf2supporting
confidence: 91%
“…In addition, in a previous study, some immunological substances in the blood were increased, but the characteristics of BUN, LDL, and HDL were not altered significantly (Cho et al, 2006). Furthermore, sows increased some immune substances in serum, and ADFI and ADG of growth performance were enhanced in the sow and nursing piglets (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 69%
“…This indicated that FSP supplementation promoted intestinal growth and development and improved intestinal morphology in broilers. Anise has been reported to improve the intestinal microbiota structure (Charal, 2014;Wang et al, 2015), and a similar effect may account for the effects of fennel on intestinal development and morphology, that is, certain active ingredients or unknown factors in fennel promote the growth of beneficial intestinal microorganisms in broilers. A healthy intestinal micro-ecosystem promotes normal intestinal tract development and ensures the integrity of the intestinal morphological structure.…”
Section: Discussionmentioning
confidence: 96%